Analisis Pengaruh Strategi Akuntansi Manajemen Terhadap Volume Penjualan pada UD Andika Saputra - Intan Karunia Devi; Indra Lila Kusuma; Sri Laksmi Pardanawati (Jurnal Ilmiah Keuangan Akuntansi Bisnis (JIKAB), 2023)
This research is a type of quantitative descriptive research which aims to determine the effect of management accounting strategies in increasing sales volume at UD Andika Saputra. The strategies studied are management accounting information systems, promotions, and product quality. The type of data used in this study was primary data in the form of a questionnaire which was distributed to samples that had been calculated using the Slovin formula and resulted in a total of 109 consumers of UD Andika Saputra. The data analysis method used in this study is Multiple Linear Regression Analysis using the SPSS test tool version 23.00. The results of data analysis show that partially the management accounting information system has no effect on sales volume. While partially promotion and product quality have a significant effect on sales volume at UD Andika Saputra. Testing the coefficient of determination (R2) shows an R2 of 0.483 which means that the variables of management accounting information systems, promotions, and product quality affect the sales volume variable by 48.3% at UD Andika Saputra. Keywords: Management accounting information system, promotion, product quality, sales volume.